SO2, NOx, HF, HCl and PCDD/Fs emissions during Co-combustion of bituminous coal and pickling sludge in a drop tube furnace. (15th December 2016) - Zhang, Shaorui; Jiang, Xuguang; Lv, Guojun; Liu, Baoxuan; Jin, Yuqi; Yan, Jianhua
Abstract: The influence of co-combustion of bituminous coal and pickling sludge on SO2, NOx, HF, HCl and PCDD/Fs emissions was studied in a drop tube furnace. To simulate the combustion condition of suspension firing boilers, the experiment was performed at 1100–1400 °C with the share of sludge in the feed ranging from 0 to 10% by weight. The combustion characteristics of coal and of blended fuels were studied by TG analysis. The results showed that the average combustion efficiency of co-combustion of bituminous coal and pickling sludge in the drop tube furnace is larger than 99%. SO2, NOx and HCl emissions had an increasing tendency with the temperature rising, but HF emissions were not sensitive to temperature. SO2 and HF emissions had a rising trend with increasing share of sludge, while NOx and HCl emissions had an opposite trend. No obvious effect of temperature and the share of sludge on the total TEQ of PCDD/Fs was found, and the emissions of the seventeen congeners were basically stable under different experimental conditions. TG results showed that the combustion characteristics of coal and blended fuels were basically the same. XRD results showed that the ash composition changed significantly with the addition of sludge. Compared to the national standard, when co-combusting of bituminous coal and pickling sludge in commercial power plant, desulphurization and denitrification equipment, activated carbon injection and baghouse should be provided.